HDAC4: mechanism of regulation and biological functions. (February 2014) - Wang, Zhengke; Qin, Gangjian; Zhao, Ting C
The acetylation and deacetylation of histones plays an important role in the regulation of gene transcriptions. Histone acetylation is mediated by histone acetyltransferase; the resulting modification in the structure of chromatin leads to nucleosomal relaxation and altered transcriptional activation. The reverse reaction is mediated by histone deacetylase (HDAC), which induces deacetylation, chromatin condensation and transcriptional repression. HDACs are divided into three distinct classes: I, II, and III, on the basis of size and sequence homology, as well as formation of distinct complexes. Among class II HDACs, HDAC4 is implicated in controlling gene expression important for diverse cellular functions. Basic and clinical experimental evidence has established that HDAC4 performs a wide variety of functions. Understanding the biological significance of HDAC4 will not only provide new insight into the mechanisms of HDAC4 involved in mediating biological response, but also form a platform to develop a therapeutic strategy to achieve clinical implications.